OVERVIEW ON PASSENGERS OVERLOAD CONTROL IN PUBLIC BUSES CASE STUDY: TANZANIA (International Journal of Engineering and Computer Science, 2017)
Passengers overload in public buses has been a problem in Tanzania. Despite some stationing police at different locations for manual check being in place, the overloading of passengers still persists. The current system doesn’t work efficiently as the check is done at random, and it is difficult during the rainy seasons and at night and it is costs and needs labor power. The findings indicate that many deaths and injuries when accidents occur, they cause deaths and injuries mainly if there is passenger overloading or if the passengers are not wearing seat belts or both. Many people lose their lives and some are severely injured when accidents occur in these public buses. This paper checks an overview on the current system and proposes a new system which uses new technology for controlling passengers overload in public buses to overcome to challenges of the current system. The proposed system will help in controlling excessive passengers and hence reduce the number of deaths and severe injuries. It will also reduce the possibilities of bribe and reduce cost and labor power. Finally the standard and comfortable passenger system for public buses can then be attained.